Attention indicator dynamics of qualified climbers influenced by hypoxic training during the overcoming various altitude levels of Mount Elbrus - Andriy Kiyko; Viacheslav Mulyk (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to determine the effect of hypoxic training on the attention indicators at different altitudes when crossing the Mount Elbrus. Material & Methods: the study of various attention indicators with the participation of control (n=16) and experimental (n=12) groups with the use of interval hypoxic training (IHT) in the 15-15 mode with breathing through the system into a confined space in the experimental group and using the methods of mathematical statistics are carried out. Result: studies have made it possible to determine that the use of the regime of discontinuous hypoxia 15-15 in the training process of the pre-competitive period contribute to an increase in attention rates that affect adaptation to the load under hypoxia conditions. Conclusion: results of the conducted studies indicate that the use of IHT in the 15-15 mode in the period before the ascent to Mount Elbrus allows to significantly increase the attention rates of qualified climbers at different altitude levels.